Pendampingan dan Pelatihan Pencatatan Keuangan pada Usaha Roti “ARIN Bakery” di Kecamatan Pungging Kabupaten Mojokerto - Armin, Rini; Setyariningsih, Eny; Akbar, Maylindah Angelina (Fakultas Ekonomi Universitas Islam Majapahit, 2021)
The Financial Recording Assistance and Training Activity at the “ARIN Bakery” Bakery Business in Pungging District, Mojokerto Regency is planned to be carried out within 6 months starting from February 1, 2021 to July 31, 2021. The objectives of the Financial Recording Assistance and Training Activities in the “ARIN Bakery” Bread Business in Pungging District, Mojokerto Regency are: (1) Increasing partners' understanding of the importance of financial records in business management; (2) Improved partner performance in general. This method of implementing Financial Recording Assistance and Training in the “ARIN Bakery” Bread Business in Pungging District, Mojokerto Regency solves the problems faced by partners, especially those related to business management based on financial records so that it can run well and sustainably.